2018
DOI: 10.1126/science.aau7761
|View full text |Cite
|
Sign up to set email alerts
|

Venoms to the rescue

Abstract: Insights into the evolutionary biology of venoms are leading to therapeutic advances

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
72
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(82 citation statements)
references
References 15 publications
0
72
0
6
Order By: Relevance
“…The acquisition of venoms and poisons is a transformative event in the evolution of an animal, because it remodels the predator-prey interaction from a physical to a biochemical battle, enabling animals to prey on, and defend themselves against, much larger animals (Holford, Daly, King, & Norton, 2018). Here we report the initial functional and structural characterization of PmPV2, a toxin that, according to the experimental results on mice and cell cultures, would be a potential defense of apple snail embryos against predation.…”
Section: Discussionmentioning
confidence: 99%
“…The acquisition of venoms and poisons is a transformative event in the evolution of an animal, because it remodels the predator-prey interaction from a physical to a biochemical battle, enabling animals to prey on, and defend themselves against, much larger animals (Holford, Daly, King, & Norton, 2018). Here we report the initial functional and structural characterization of PmPV2, a toxin that, according to the experimental results on mice and cell cultures, would be a potential defense of apple snail embryos against predation.…”
Section: Discussionmentioning
confidence: 99%
“…They are used for defense, predation or competitor deterrence, but in all cases they are physiologically expensive traits that have been optimized by strong selective pressure for specific functions. This evolutionary streamlining often results in high selectivity and target-specific bioactivity, meaning that animal venoms are now considered valuable bioresources in the field of drug discovery (Holford et al, 2018). Several blockbuster drugs have been derived from venom components (Holford et al, 2018), but they were also investigated as research tools, cosmetics, industrial enzymes or bioinsecticides (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This evolutionary streamlining often results in high selectivity and target-specific bioactivity, meaning that animal venoms are now considered valuable bioresources in the field of drug discovery (Holford et al, 2018). Several blockbuster drugs have been derived from venom components (Holford et al, 2018), but they were also investigated as research tools, cosmetics, industrial enzymes or bioinsecticides (e.g. Duterte and Lewis, 2010;Pennington et al, 2018;Dongol et al, 2019;Saez and Herzig, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Venomous species are extremely diverse and ubiquitously evolved in all known animal phyla, as for example in old lineages such as marine cnidarians, molluscs, or polychaetes, but also terrestrial groups like reptiles, all major arthropod clades and even mammals Dutertre et al, 2014;von Reumont et al, 2014a,b). It is estimated that around 200,000 animal species (Holford et al, 2018) use venom as the utmost important molecular trait that guarantees the fitness and survival of species being employed for defense, predation, and competition von Reumont et al, 2014a;Sunagar et al, 2016), see also Figure 1. In contrast to poisons, which are generally composed of less complex mixtures of toxic substances and used in a rather unspecific manner, venoms are constituted by complex toxin components such as peptides, proteins, and other smaller organic molecules (Fry et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The production of an effective antidote is largely dependent on the present knowledge of a species' venom cocktail and possible intra-specific variation in its toxin components (Chippaux et al, 1991;Gutiérrez et al, 2009). Another motivation behind many studies in venomics is to screen for and to harvest the potential of identified venom proteins (single toxins) for applied research, such as the development of highly specific agrochemicals like bio-insecticides or pharmaceutical applications and drug design (Windley et al, 2012;King and Hardy, 2013;Holford et al, 2018;Pennington et al, 2018;Senji Laxme et al, 2019).…”
Section: Introductionmentioning
confidence: 99%